DevOps Paradox - Farcic, Viktor; Farcic, Viktor (Packt Publishing, 2019)
Discover DevOps secrets from leading experts. Viktor Farcic interviews DevOps industries voices including Mike Kail, Greg Bledsoe, Jeff Sussna, James Turnbull, Kohsuke Kawaguchi, Liz Keogh, and more. Key Features Leading DevOps experts share their insights into modern DevOps practice Engage with the real-world challenges of putting DevOps to work Strengthen your DevOps practices now and prepare for future DevOps trends Book Description DevOps promises to break down silos, uniting organizations to deliver high quality output in a cross-functional way. In reality it often results in confusion and new silos: pockets of DevOps practitioners fight the status quo, senior decision-makers demand DevOps paint jobs without committing to true change. Even a clear definition of what DevOps is remains elusive. In DevOps Paradox, top DevOps consultants, industry leaders, and founders reveal their own approaches to all aspects of DevOps implementation and operation. Surround yourself with expert DevOps advisors. Viktor Farcic draws on experts from across the industry to discuss how to introduce DevOps to chaotic organizations, align incentives between teams, and make use of the latest tools and techniques. With each expert offering their own opinions on what DevOps is and how to make it work, you will be able to form your own informed view of the importance and value of DevOps as we enter a new decade. If you want to see how real DevOps experts address the challenges and resolve the paradoxes, this book is for you. What you will learn Expert opinions on: Introducing DevOps into real-world, chaotic business environments Deciding between adopting cutting edge tools or sticking with tried-and-tested methods Initiating necessary business change without positional power Managing and overcoming fear of change in DevOps implementations Anticipating future trends in DevOps and how to prepare for them Getting the most from Kubernetes, Docker, Puppet, Chef, and Ansible Creating the right incentives for DevOps success across an organization The impact of new techniques, such as Lambda, serverless, and schedulers, on DevOps practice Who this book is for Anybody interested in DevOps will gain a lot from this book. If you want to get beyond the simplistic ideals and engage with the deep challenges of putting DevOps to work in the real world, this book is for you.